Review: The Role of Radiolabeled DOTA-Conjugated Peptides for Imaging and Treatment of Childhood Neuroblastoma - Alexander, Natasha; Vali, Reza; Ahmadzadehfar, Hojjat; Shammas, Amer; Baruchel, Sylvain (Current Radiopharmaceuticals, 2018)
Background: Childhood neuroblastoma is a heterogenous disease with varied clinical presentation and biology requiring different approaches to investigation and management. Metaiodobenzylguanidine (MIBG) is an essential component of metastatic staging for neuroblastoma and has been used as a treatment strategy for relapsed and refractory neuroblastoma. However, as 10% of children with neuroblastoma will have 123I-MIBG non-avid imaging and up to 60% with relapsed and refractory neuroblastoma will require further treatment with 131I-MIBG, alternative radioisotopes have been investigated for imaging and treatment. Neuroblastoma tumors express mostly somatostatin receptor- 2 (SSTR2) that can be targeted by somatostatin analogues including DOTA-conjugated peptides e.g. DOTATATE, DOTATOC. Objectives: This review summarizes the rationale, utility and experience of DOTA-conjugated peptides in imaging and treatment of childhood neuroblastoma. Results and Conclusions: Radiolabeled DOTA-peptides are used routinely in adults to image neuroendocrine tumors and have potential to be used to image and treat neuroblastoma. 68Ga-DOTATATE PET/CT has been shown to have better sensitivity, quicker clearance and administration times, reduced radiation exposure and limited toxicity compared to 123I-MIBG. Therapeutic studies of peptide receptor radionuclides e.g. 177Lu-DOTATATE in patients with relapsed neuroblastoma have used 68Ga- DOTATATE PET/CT to determine eligibility for therapy. Further studies would need to investigate appropriate indications, timings, scoring and clinical significance of radiolabeled DOTA-peptide conjugated PET/CT imaging in childhood neuroblastoma.
Keywords: radionuclide imaging